No-arbitrage Near-Cointegrated VAR(p) term structure models, term premia and GDP growth - Jardet, Caroline; Monfort, Alain; Pegoraro, Fulvio (Journal of Banking & Finance, 2013)
The recent macro-finance literature does not agree either about the empirical properties of the expectation part and of the term premium on long-term bonds or about the importance or even the direction of the relationship between the term premium and future economic activity. This paper proposes a two-step approach to handle both problems. First, in a VAR setting, we extract a reliable measure of the term premium by means of averaging estimator techniques aiming at optimally solving prediction problems when highly persistent processes are present and, thus, providing a so called Near-Cointegrated VAR(p) approach. Second, we analyze the dynamic response of GDP to shocks to the term premium by using the New Information Response Function concept. As far as the first problem is concerned, we find that the NCVAR-based term premium measure is rather stable and counter-cyclical, as suggested by interest rates survey-based estimation of yield curve models and by its risk compensation role. Regarding the second problem, we find that an increase in the long-term spread caused by the term premium induces two effects on future economic activity: the impact is negative for short horizons (less than 1year), whereas it is positive for longer ones.